SOGOL –An Experiential Learning (Students Own Gadget for Outstanding Learning) - Bajaj, Sunil (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Children are not machines. They think but machines do not think. Children have interest and machines do not have interest. They work only as programmed. As children think so we should provide interesting and challenging opportunity so that they can think, analyse make rule and learn. Sogol is one of interesting TLM for this. In the NCF -2005, it is emphasized to follow child centered approach with a view that every child canlearn Mathematics. But we know that Children learn only when they are interested. Creating interest is a big challenge for teachers. In NCF-2005, it is also expected that teachers should act as facilitators for learning by doing. They should think and give interesting opportunities with appropriate challenge to all children in which they learn through their own experiences. They may be able to think logically and independently and find rules themselves with their own experiences. This experiential learning may be by doing activities with or without using TLM or items of daily life or playing games or puzzles